On the reflection of Alfvén waves in an ideal magnetoatmosphere - Hadi Yahya Alkahby; M. A. Mahrous (International Journal of Mathematics and Mathematical Sciences)
A lineafized theory ofmagnetoatmospheric waves is developed where the restoring forces are those of compressibility and magnetic pressure. An equation for resonance is derived. Reflection and tunneling of upward propagating Alfvén waves in an ideal Magnetoatmosphere are considered. It is shown that the magnetic field produces a reflecting nonabsorbing critical layer. Below the critical layer, the solution of the problem can be written as a linear combination of an upward and a downward propagating wave and above it the solution decays exponentially with the altitude. The location of the critical layer and the magnitude of the reflection coefficient are determined and the conclusions are discussed in cormeetion with the heating mechanism of the solar atmosphere